Design of a Soil Erosion Warning System in Watersheds Based on Arduino Uno - M. Ulud Risaldi; Ahmad Raditya Cahya Baswara (Universitas Ahmad Dahlan, 2023)
Tropical climate conditions with two seasons, namely rainy and hot in Indonesia and coupled with relatively diverse surface and rock topography conditions, have the potential for natural disasters, one of which is erosion in watersheds. Making the system using the Arduino Uno microcontroller, SIM-800L V2 Module, Piezoelectric Sensor, Soil Moisture Sensor, Buzzer and LCD. The designed system will be able to display information on the spot, and can send via SMS. In pre-erosion conditions, there are two variables used, namely soil moisture and soil vibration. As for post-erosion, it only takes the soil vibration variable. The limit value of vibration in pre-erosion conditions is 31%. Pre-erosion data is divided into 3 statuses, namely BEWARE at humidity values of 31-70% and vibration values of 5-15%, DANGER status with humidity values of 71-100% or vibration values of 16-30%, and other than that they are included in the SAFE category. Whereas in post-erosion 3 categories are LIGHT EROSION at vibration values of 31-50%, MODERATE EROSION 51-70% and SEVERE EROSION 71-100%.